Kemampuan Aparat Pekon Dalam Menyelenggarakan Administrasi Pemerintahan: Studi Pada Aparat Pekon Gunung Sugih Kecamatan Balik Bukit Kabupaten Lampung Barat - Mustain, Mustain (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2021)
Development is one of the capital or means to achieve the progress of the nation and the State, both in the form of physical and non-physical development. Development that is carried out must adhere to the principle of fairness and equity. For this reason, the village as the lowest form of government becomes the central point or target in implementing development. In order for the implementation of development in the village to run well and in an orderly manner, it requires quality human resources for village government officials who understand what their duties and responsibilities are as village government officials. In order to achieve development goals in the village, village government officials are required to be able to develop themselves with all the existing limitations, so that it is hoped that the natural resources in each village can be used as capital in achieving successful development in the village. In addition, village government officials are required to carry out an orderly administration related to government activities in the village. Orderly government administration is a task that must be carried out as well as a reference for successful development in a village. The results showed that the level of the village government apparatus capacity in carrying out village government administration in Pekon Gunung Sugih, Balik Bukit District, West Lampung Regency was in the high category. Based on the calculation of the interval obtained from the answers of each respondent to the questionnaire given, the ability of village government officials to carry out village government administration in Pekon Gunung Sugih, Balik Bukit sub-district, West Lampung Regency is 60%, meaning that the level of ability to carry out orderly administration of village government officials in Pekon Gunung Sugih, Balik Bukit District, West Lampung Regency is quite good. From the results of research in the field and in order to improve orderly village government administration, there are still village officials or respondents who have not implemented an orderly village government administration. For this reason, in order to achieve successful development and an orderly village administration administration, the parties concerned are expected to immediately carry out improvements and socialization related to administrative activities in the village.